United Nations : Keeping the Peace - Sean Connolly (United States Raintree, 2003)
Describes the work of the United Nations, historical reasons for its development, effects of the Cold War on UN peacekeeping efforts, and modern and future uses of UN peacekeeping forces.
Keywords: PY-UOI-How We Organize Ourselves